(untitled) (Journal of Libya for geographical studies, 2022)
This research aims to study the thermal characteristics of the Ghadames station for the period from 1971-2020 AD, by analyzing the monthly, seasonal and annual temperature data, and knowing its trend line, and then revealing the rate of change in the seasonal and annual rates of temperature in Ghadames during the two study periods (1971). -1995) and (1996-2020), using the. test analysis (T-Test), based on the statistical program SPSS to find out the significance of the difference in the annual and quarterly averages between the two study periods. The results of the t-test indicated that there was no difference in the annual average temperature between the two study periods in favor of the second period (1996 - 2020), as it did not exceed 0.92 °C, which is not a statistically significant difference, as the value of the statistical significance reached 0.182, which is greater than the level of statistical significance 0.05, which is accepted The null hypothesis that the average of the first period is equal to the mean of the second period. With the emergence of a noticeable change in the seasonal rates of temperature, reaching its maximum change in the summer, where the increase for the second period was a difference of 6.6 m compared to the first period and at a level of statistical significance less than 0.05.